TOURISM POTENTIALITY OF HIGH RANGE AREAS OF KERALA - A CASE STUDY OF WAYANAD DISTRICT - SURESH A AND AYOOB C P (AJRSH: JOURNAL OF RESEARCH IN SOCIAL SCIENCE & HUMANITIES, 2012)
Kerala is well known for tourism and the state tourism is marketed as “God’s own country’. The topography climate, natural beauty flora and fauna- all adds to the tourism potentiality of the small state which lies in the southern peninsula part of India .During the year 2011, 85 lakh domestic tourists and 6.61 lakh foreign tourists visited the state registering of 8.61% increase in domestic tourism and 18.3%increase in foreign tourism over the previous year. During the period 2005 to 2010 contribution of tourism to the state exchequer has increased considerably .Total revenue generated(Direct and indirect) increased from Rs.4500 crores in 2001 to 17348 crores in 2010. In spite of this fact, it is observed that tourism potentiality of the state is not evenly and properly utilised in the state. It becomes more true in the case of Malabar area and highrange areas of Kerala.Idukki and Wayamad are the two high range areas of Kerala. This study examined the tourism potentiality of Wayanad and highlighted the factors based on which suitable tourism products can be developed. The study also reveals the ecotourism prospects of the state.